Development of Screen Inks from Black Soil and Red Soil using Natural Mordant - Theamdee, Pawinee; Wongsa-ard, Thanita (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This research aims to develop printing ink and optimal conditions for screen printing on cotton fabric using natural colorants from black and red soil. The colorant powder, comprising 10 g, was blended with a prepared printing powder of 40 g at room temperature. Screen printing was conducted on cotton fabric, examining the impact of color-baking durations at intervals of 0, 5, 10, and 15 min at a temperature of 150 oC. Additionally, the effects of two different mordants such as Marl and sodium chloride at a 10% w/v concentration, were investigated concerning color fastness during washing, exposure to bleaching agents, sunlight, and abrasion resistance. The results of testing indicated that the cotton fabrics screen-printed with black and red soil colors with baked for 15 min exhibited the best colorants. When Marl was used as a mordant, the colors appeared richer, while sodium chloride produced brighter hues. The mordant from Marl exhibited superior color fastness for cotton fabrics screen printing with black and red soil colors. Furthermore, these colors with excellent durability could be screen-printed on various cotton fabric products.